Study of Antibacterial, Antioxidant Activity and Biochemical Parameters of Different Honey Samples - Hussein, Jian Lateif; Ahmed, Akhter Ahmed; Raheem, Dotsha Jaleel (Iraqi Journal of Science, 2023)
The present study was undertaken to determine and compare the antibacterial and biochemical characteristics of honey samples from Kurdistan region in Iraq and Arabian Gulf region. Sixteen honey samples of mixed floral origins from both regions were analysed and compared. Antibacterial activity of the honey samples was investigated against five clinical pathogenic bacteria: Acinetobacter baumannii, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi and Staphylococcus aureus by agar dilution method. Both sample sets showed differential biochemical characteristics and potential functional properties such as antioxidant and antimicrobial properties. All measured parameters were within accepted ranges. However, significant differences were found in mean±SE levels of conductivity and pH, diastase activity, TPC and DPPH activity between the two sample groups with KRI samples showing more desirable qualities. Other parameters such as water content, total acidity, total and reducing sugars, sucrose and HMF showed no significant difference. The results of antibacterial activity indicated that KRI honey is more effective than AG honey against the tested pathogenic bacteria.